Behavioural responses of Vespula germanica (Hymenoptera: Vespidae) wasps exposed to essential oils - Buteler, Micaela (2015)
Secondary plant metabolites such as those present in essential oils can be toxic to herbivorous insects and also repel attack, given they play a role in selection and acceptance of host plants. However, few studies have dealt with the use of plant-based repellents to manage invasive wasps. The objective was to assess essential oils with potential as wasp repellents, and to gain further insight as to how they affect the learning capacities of these insects. Five essential oils were tested on Vespula germanica (Fabricius) wasps in field choice and no-choice tests. When given a choice, foragers avoided the treated baits almost completely. Wind tunnel bioassays demonstrated that wasps recognise the repellent essential oils through olfactory cues, leading to a dose-dependent decreased response to the food stimulus. The effect of the repellents on the cognitive ability of V. germanica workers was also studied in relation to food search efficiency. Naive workers landed on the treated baits, although it took them longer than to land on control baits. When workers were allowed to forage on a food bait twice before a repellent was added, an effect on relocation behaviour was observed. The returning workers arriving to a feeding site with essential oil were reticent to land on it, suggesting that there is indeed a repellent effect and not just masking of the food source. A push–pull system combining attractive baits with the use of plant-based repellents is a promising management strategy in urban settings for this insect pest.